2014
DOI: 10.3347/kjp.2014.52.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Haemadipsa rjukjuana (Hirudiniformes: Haemadipsidae) in Gageo Island, Korea

Abstract: There are 60 species of blood-feeding land leeches, 50 species belonging to the family Haemadipsidae and 10 species belonging to the family Xerobdellidae. Despite recent papers on the land leeches, their taxonomic identification is not fully understood, especially at a species level. In Korea, there have been no historical records of the terrestrial leeches, but recently an unrecorded blood-feeding land leech was discovered at Gageo-do (Island), Korea. Molecular analysis was used to identify the species of 29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…ornata is distributed in Sumatra and northeastern India (Bandyopadhyay & Mandal, ; Borda & Siddall, ); H . rjukjuana is distributed in the Indochinese Peninsula, Malay Peninsula, Indonesia, Gageodo Island of Korea, and Ryukyu Islands of Japan (Lai et al, ; Won et al, ); and H . montana is distributed in south and northeastern India (Bandyopadhyay & Mandal, ; Borda & Siddall, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ornata is distributed in Sumatra and northeastern India (Bandyopadhyay & Mandal, ; Borda & Siddall, ); H . rjukjuana is distributed in the Indochinese Peninsula, Malay Peninsula, Indonesia, Gageodo Island of Korea, and Ryukyu Islands of Japan (Lai et al, ; Won et al, ); and H . montana is distributed in south and northeastern India (Bandyopadhyay & Mandal, ; Borda & Siddall, ).…”
Section: Methodsmentioning
confidence: 99%
“…The family Haemadipsidae, whose members are known for their blood‐feeding habits, comprises <70 species and is highly diverse, especially in tropical regions with high humidity in Indo‐Pacific rainforests (Borda & Siddall, ). The genus Haemadipsa , a member of Haemadipsidae, is very abundant in Southeast Asia (Won et al, ). Haemadipsa japonica Whitman (Haemadipsidae) is endemic to Japan (Figures and ); it is distributed in Honshu, Shikoku, and Kyushu (Aizawa & Morishima, ; Borda & Siddall, ; Whitman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our leech cox1 sequences were combined with cox1 data from prior phylogenetic studies of Haemadipsidae and GenBank (Borda et al, 2008;Borda & Siddall, 2010;Lai et al, 2011;Tessler et al, 2016;Won et al, 2014). Fully redundant sequences were then removed using the 'fastx_collapser' tool from the FASTX-Toolkit (http://hannonlab.cshl.edu/fastx_toolkit), as they can have negative impacts on the topological stability of maximum likelihood reconstructions and ultimately do not provide any additional information.…”
Section: Systematics and Biodiversitymentioning
confidence: 99%
“…It is aged for 20 months from natural garlic in order to reduce its harsh, irritating taste and smell. Nevertheless, this AGExt has a higher concentration of sulphur-containing compounds such as alliin and S-allyl cysteine (SAC) that is a potent antioxidant and free radical scavenger [10]. Recent studies in the author's laboratory have shown that AGExt is an effective inhibitor of AGEs in vitro.…”
Section: Introductionmentioning
confidence: 99%